Ecological Correlates of Range Size in the Tent-Making Bat Artibeus watsoni - Chaverri Echandi, Gloriana (2007)
We examined variation in foraging- and roosting-range size in the tent-making bat Artibeus watsoni. We radiotracked 42 individuals at 2 sites in the Golfito Wildlife Refuge and 6 sites at Corcovado National Park, southwestern Costa Rica. Average home-range size of A. watsoni was the smallest recorded for a bat species (3.6 ha). Site, age, reproductive status, habitat, and season all had significant effects on foraging ranges, but sex and population abundance did not. Bats from the most productive sites, such as primary forests, had smaller foraging ranges, and subadults ranged farther than adults. During the dry season, females in late pregnancy had the smallest foraging ranges of all, most likely as a result of flight constraints imposed by the large fetus and an increase in fruit availability. Conversely, lactating females sampled during the early rainy season had among the largest foraging ranges. Males had significantly smaller roosting ranges than females, and adult bats sampled from areas of low roost abundance and high population abundance had smaller roosting ranges. However, subadults appeared to be unaffected by such changes in resource abundance, perhaps because they often roost in unmodified leaves. Although differences in resource availability and competition were important in determining roosting-range size, these effects were concealed by effects of reproductive activities such as mating, pregnancy, and lactation. Reproductive condition, along with foraging and roosting resource abundance, were largely responsible for determining ranging patterns in A. watsoni, but factors influenced foraging- and roosting-range size in different ways.